A key and checklist to the Neotropical forensically important "Little House Flies" (Diptera: Fanniidae) - Diana Grisales; Melise C. Lecheta; Fernando H. Aballay; Claudio J.B. de Carvalho (Zoologia (Curitiba))
ABSTRACT Fanniidae (Insecta: Diptera) is a relatively small family (ca. 350 spp.) with five genera, of which Fannia Robineau-Desvoidy, 1830 and Euryomma Stein, 1899 have Neotropical distributions. Some of these species are almost always found in forensic studies. Forensically relevant species have been neglected, despite recent forensic studies that suggest their importance for estimating post-mortem interval (PMI). Thus, current and updated keys to identify adults or larvae on carcasses are unavailable for the most important species. While immature stages are important in estimating PMI, evidence suggests that adults (Fanniidae as well as other families) may also be useful for this purpose. Here we provide a key to males of the species of Fanniidae (found on corpses and other decomposing organic matter) with a checklist of species that have been used in forensics in the Neotropical region. The key comprises all 38 species of Fannia and Euryomma that have already been successfully used in forensics, and species that are potentially useful for estimating PMI. These records were found after reviews of the literature and data from entomological collections. Photographs and illustrations of the main characters in the key are provided.